Outcomes of lateral and posterior approaches in hip arthroplasty: A cohort from low-middle-income country - Usman Ali; Eisha Saadat; Sher Baz Khan; Muhammad Musa Hamza; Syed Waqas; Anum Ali; Ahmed Raheem; Junaid Khan (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the postoperative outcomes and complications of the posterior approach and lateral approach for total hip arthroplasty in resource-limited settings. Method: The retrospective cohort study was conducted at Aga Khan University Hospital, Karachi, from January to July 2024, and comprised data of patients who underwent total hip arthroplasty between January 2014 and December 2019. Key outcomes noted in both posterior approach group A and lateral approach group B were postoperative complications, blood loss, transfusion rates, and length of hospital stay. Data was analysed using STATA 15. Results: Of the 498 patients, 402(80.7%) were in group A with median age 60 years (interquartile range: 45-70 years), and 96(19.3%) were in group B with median age 55.5 years (interquartile range: 42-69.5 years) (p>0.05). Group B showed higher blood loss and transfusion rates compared to group A (p<0.05). Postoperative complications were significantly more frequent in group B than group A (p<0.05), with infection being the most common 25(5%) patients across the groups. Group A had significantly lower adjusted odds of complications compared to group B (adjusted odds ratio: 0.51; 95% confidence interval: 0.26-0.98). Conclusions: The posterior approach for total hip arthroplasty was associated with lower blood loss, fewer transfusions and reduced complication rates compared to the lateral approach, making posterior approach a preferred surgical technique in resource-limited settings. Key Words: Total hip arthroplasty, Postoperative complications, Posterior approach, Lateral approach, Surgical outcomes, Orthopaedic surgery, Resource-limited settings, Hip fracture, Surgical technique, Patient recovery.